Polyacrylic acid-coated iron oxide nanoparticles could be a useful tool for tracking inflammatory monocytes (2019)
ABSTRACT: Aim: To establish the effect of poly(acrylic acid)-coated iron oxide nanoparticles (PAC-IONs) and later exposure to a magnetic field on the differentiation of mononuclear phagocytes into macrophages. Methods: By flow cytometry, cell death was evaluated with DIOC6 and PI, Poly (ADP-ribose) Polymerases (PARP) fragmentation, H2AX phosphorylation and TUNEL assay. Cytokines by Cytokine bead array and the intracellular amount of iron by atomic absorption spectrometry. Results: PAC-IONs did not induce apoptosis, modify the cell membrane integrity or alter the mitochondrial membrane potential. They did not affect the cell morphology, the pattern of cytokine accumulation or the activating role of differentiation of mononuclear phagocytes into macrophages on the proliferation of autologous T cells. Conclusion: This evidence indicates that the PAC-IONs are safe and biocompatible. Moreover, the selectivity of the PAC-IONs for mononuclear phagocytes, as well as their increased uptake by non-classical monocytes, warrant future research with a view to their use as a contrast agent, a useful tool for in vivo tracking of tissue-infiltrating mononuclear phagocytes.